Analysis of Digital Marketing, Service Quality, Donation Interest, and Trust on Zakat, Infaq, and Sedekah Payments at BAZNAS Pohuwato Regency - Karundeng, Deby R.; Yakup, Yakup; Ibrahim, Meimoon; Pratama, Dody (International Journal Of Education, Social Studies, And Management (IJESSM), 2025)
This study analyzes the influence of digital marketing, service quality, donation interest, and trust on zakat, infaq, and sedekah payments at BAZNAS Pohuwato Regency. The population for this research consists of 68 active zakat obligors and zakat, infaq, and sedekah donors registered at BAZNAS Pohuwato. The research method used is multiple linear regression analysis. The results of the study conclude that digital marketing, service quality, donation interest, and trust all have a positive and significant impact on the decisions to pay zakat, infaq, and sedekah at BAZNAS Pohuwato Regency. Each of these factors plays an essential role in encouraging the community to participate in zakat payments in a more accessible and effective manner.